PENGARUH PEMBERIAN BUKU SAKU TERHADAP PENGETAHUAN SKRINING FAKTOR RESIKO HIPERTENSI PADA REMAJA PUTRI SMA - Pamungkas, Atik Mahmudah Aji; Hanung, Allania; Nuraeni, Nuraeni (Poltekkes Kemenkes Maluku, 2023)
The World Health Organization indicates that non-communicable diseases are by far the leading cause of death worldwide, representing 63% of all annual deaths. The number of new cases that occurred in Boyolali II was 8,444 people with hypertension. It is important to carry out early screening since adolescence, this is because women will experience pregnancy, and later if teenagers experience hypertension, during pregnancy they will be at risk of suffering from preeclampsia. The aim of this research was to see whether there was an effect of giving pocket books on knowledge of screening for hypertension risk factors among female students at SMA 2 Boyolali. This type of research is quantitative research using a pre-experimental design using the Wilcoxon bivariate test. The population in this study was female students at SMA 2 Boyolali for the 2021/2022 academic year, totaling 317 with a quota sampling technique of 90 people using the Slovin formula. The conclusion of this research is that health education has an influence on knowledge of screening for hypertension risk factors in teenage students at SMA 2 Boyolali (0.000<0.05). By providing health education as an effort to increase knowledge from an early age regarding screening for hypertension risk factors. It is hoped that the results of this research can provide input to young students, especially young female students at SMA 2 Boyolali, to gain more knowledge about hypertension so that they can help avoid things that should not be consumed or done to avoid hypertension from an early age.